Dual-wavelength responsive photoelectrochemical aptasensor based on ionic liquid functionalized Zn-MOFs and noble metal nanoparticles for the simultaneous detection of multiple tumor markers. Issue 45 (10th November 2021) - Zhong, Yingying; Wang, Xian; Zha, Ruyan; Wang, Chen; Zhang, Huijuan; Wang, Yanying; Li, Chunya
Abstract : A dual-wavelength responsive photoelectrochemical aptasensor based on ionic liquid functionalized Zn-MOF microspheres and noble metal nanoparticles was constructed for CEA and CA153 determination with high performances. Abstract : A single tumor marker may correspond to a variety of diseases, and a specific disease requires the joint detection of multiple tumor markers for improving the accuracy of diagnoses. An ionic liquid-functionalized metal–organic framework (Zn-MOF microspheres) was used as the substrate to capture the aptamer (Ab1), and noble metal nanoparticles were used to label a signal aptamer (Ab2) to construct a dual-wavelength responsive sandwich-type photoelectrochemical (PEC) aptasensor. Due to the size effect, plasma resonance and the response of the noble metal nanoparticle enhancement system to different excitation wavelengths, the simultaneous detection of CEA and CA153 tumor markers was realized. Under the optimized conditions, CA153 and CEA at concentrations of 0.05–100 U mL −1 and 0.005–10 ng mL −1 were detected by the PEC aptasensor. Detection limits calculated for CA153 and CEA determinations were 0.0275 U mL −1 and 2.85 pg mL −1 (S/N = 3), respectively. CA153 and CEA in serum samples were detected by the PEC aptasensor, and their concentrations were well consistent with that obtained from the ELISA. In addition, the PEC aptasensor exhibited a recovery rate of 96.98%–103.4%, and a relative standard deviation of 1.1%–3.6%, indicating good practical value and accuracy, further confirming its potential for clinical diagnosis.